2015
DOI: 10.3892/ol.2015.3580
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory drugs and uterine cervical cancer cells: Antineoplastic effect of meclofenamic acid

Abstract: Abstract. Uterine cervical cancer (UCC) is one of the main causes of cancer-associated mortality in women. Inflammation has been identified as an important component of this neoplasia; in this context, anti-inflammatory drugs represent possible prophylactic and/or therapeutic alternatives that require further investigation. Anti-inflammatory drugs are common and each one may exhibit a different antineoplastic effect. As a result, the present study investigated different anti-inflammatory models of UCC in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…FFA has slight to moderate toxicity (10-40% of cell death corresponding to 100 µM) in uterine cervical cancer cell lines. 58 The present study demonstrated that FFA had moderate anti-tumor activity (30-40% of cell death corresponding to 50 µg/mL) in 4T1/luc or HepG2 cells. FFA can also be used as a free radical scavenger and gap junction blocker in cancer cells.…”
Section: Discussionsupporting
confidence: 47%
“…FFA has slight to moderate toxicity (10-40% of cell death corresponding to 100 µM) in uterine cervical cancer cell lines. 58 The present study demonstrated that FFA had moderate anti-tumor activity (30-40% of cell death corresponding to 50 µg/mL) in 4T1/luc or HepG2 cells. FFA can also be used as a free radical scavenger and gap junction blocker in cancer cells.…”
Section: Discussionsupporting
confidence: 47%
“…In the context of its antitumor activity, butein is reported to downregulate metastatic protease and angiogenic factor expression of prostate cancer cells ( 41 ) and chemokine receptor expression and function of breast and pancreatic tumor cells ( 16 ), mainly through inactivating NF-κB signaling. Increasing evidence also supports the notion that anti-inflammatory drugs may also confer anti-neoplastic effect against uterine cervical cancer or HPV-dependent neoplasia ( 42 ). This raises the possibility that the combination strategy of using anti-inflammatory and conventional anti-tumor drugs may confer higher sensitivity to some types of tumors.…”
Section: Discussionmentioning
confidence: 75%
“…Several RNA demethylases inhibitors have already been developed with a potent anticancer effect. More particularly, FTO inhibitors, meclofenamic acid (MA), or its ethyl ester form (MA2) have been recently identified as specific FTO inhibitors that have shown antitumor activity on myeloid leukemia (AML) and GBM, prostate, and uterine cervical cancers [ 12 , 53 , 54 , 55 , 56 ]. R-2-hydroxyglutarate (R-2HG), an oncometabolite resulting from the conversion of α-ketoglutarate by mutant IDH1/2 enzymes, has also been shown to specifically inhibit FTO and proliferation of leukemic or GBM cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%